Effect of high‐pressure processing on the microbial load and functionality of sugar‐cookie dough. Issue 1 (6th December 2020) - Sabillón, Luis; Stratton, Jayne; Rose, Devin; Eskridge, Kent; Bianchini, Andréia
Abstract: Background and objectives: Refrigerated dough products have the potential to be a safety hazard to consumers because they could be consumed raw or undercooked. The objectives of this study were designed to evaluate the microbial and functionality changes in high pressured sugar‐cookie dough as a function of a w (0.80–0.87), pressure level (100–600 MPa), and holding time (1–6 min). Findings: Endogenous microbial populations were marginally reduced (0.2–0.5 log CFU/g) by pressure treatments. However, treating the dough at 600 MPa for 6 min significantly reduced counts of inoculated Escherichia coli by as much as 2.0 log CFU/g. Increasing the a w of cookie dough from 0.80 to 0.87 did not play a significant role in the reduction of microbial counts; however, it yielded a softer and thicker cookie when baked. Dough and cookie physical characteristics did not differ significantly among HPP‐treated and control doughs within the same a w level. Conclusions: The results of this study suggest that pressure treatment has the potential to improve the microbiological quality of wheat‐based cookie doughs. However, variations in food matrix composition must be considered because some food constituents, such as sugar and fat, may protect microorganisms against pressure‐induced inactivation. Significance and novelty: The results reported here have practical implications for the food industry and contributes to understand the effects of high‐pressure processing on wheat‐based cookie doughs and their microbial loads.